The effects of PGF2α and CIDR on ovarian antral follicular development and plasma IGF-1 concentration in Goats - Mohd Azam Khan Goriman Khan; Muhammad Modu Bukar; Omar Mohammed Ariff; Rosnina Yusoff (2011)
The aim of this study was to determine the effects of oestrus synchronization with PGF2α and CIDR on the ovarian antral follicle population and plasma IGF-1 concentration in goats. Daily transrectal ultrasonographic examination was conducted in 24 regularly cycling goats that were divided equally into 3 groups and oestrus synchronized with PGF2α (group A), CIDR (group B) and unsynchronized group (C). The mean number of follicles and IGF-1 concentration was significantly higher in the synchronized and subsequent natural oestrous cycles of group A and B when compared to group C. The total number of 3 mm diameter follicles were significantly higher in groups A and B compared with the control group C while the follicles that were 6 mm and larger were not significantly different (p>0.05). There was a significant low positive correlation (r = 0.14, N = 234) between IGF-1 concentration and the number of 3 mm follicles and between plasma IGF-I concentration and number of follicles (r = 0.13, N = 234). In conclusion, oestrus synchronization with PGF2α or CIDR was associated with increased plasma IGF-1 concentration and number of follicles compared with naturally cycling goats.